Peran Lembaga Inisiatif Zakat Indonesia di Surabaya dalam Meningkatkan Pendapatan Mustahik Melalui Program Lapak Berkah - Ubaidillah, Zaki Khoifin; Rohman, Abdur (SAFE-Network, 2024)
There are so many mustahik who experience difficulties in setting up and developing a business, so that this can lead to economic difficulties and poverty, therefore this study aims to find out the role of the Indonesian Zakat Initiative in increasing mustahik's income through the lapakkah program. This study uses a qualitative research method that is descriptive narrative. This research is a program to increase the income of Mustahik Surabaya through the Blessing Stalls program at IZI. The results of this study indicate that the role of the Indonesian Zakat Initiative Institute in Surabaya in increasing mustahik's income through the Bukalapak Berkah program, the lapak-barkah program by IZI greatly influences the business development of mustahik. The existence of the lapak blessing program from the IZI institution can help overcome the problems of mustahik who lack capital to set up and develop their business.